Sialidase Deficiency in Porphyromonas gingivalis Increases IL-12 Secretion in Stimulated Macrophages Through Regulation of CR3, IncRNA GAS5 and miR-21 - Yang, Xue; Pan, Yaping; Xu, Xiaoyu; Tong, Tong; Yu, Shiwen; Zhao, Yue; Lin, Li; Liu, Jingbo; Zhang, Dongmei; Li, Chen (Frontiers in Cellular and Infection Microbiology, 2018)
Porphyromonas gingivalis (P. gingivalis) is a major periodontal pathogen that can induce an immune response leading to a destructive inflammatory process. During the inflammatory process, interleukin-12 (IL-12) is secreted, correlating with bacterial clearance by macrophages. Bacterial sialidase has recently been shown to influence the synthesis and modification of the macromolecules on its surface, and is associated with the interaction between bacteria and host cells. We have previously constructed a P. gingivalis sialidase gene mutant strain in P. gingivalis W83 (ΔPG0352) and found that ΔPG0352 showed less pathogenicity than the wild-type strain. In this study, U937-differentiated macrophages were stimulated by P. gingivalis W83, ΔPG0352 or PG0352 complemented strain (comΔPG0352). Transmission electron microscopy showed that P. gingivalis caused a loss of membrane integrity in macrophages and the intracellular bacteria were enclosed within endocytic vacuoles. The expression of both IL-12p35 and IL-12p40 genes and the levels of IL-12p70 were significantly higher in U937 stimulated by ΔPG0352 than in those with P. gingivalis W83 and comΔPG0352. In order to explain why ΔPG0352 induced more IL-12 in macrophages, immunofluorescence assays, PCR arrays, and gene silence or overexpression experiments were carried out. Immunofluorescence assays showed that ΔPG0352 induced lower expression of CR3 in macrophages. After CR3 was suppressed, there were no significant differences in the IL-12p70 levels between macrophages stimulated by P. gingivalis W83, ΔPG0352 or comΔPG0352. PCR array experiments showed that miR-21 and lncRNA GAS5 were differentially expressed between macrophages stimulated by P. gingivalis W83 and ΔPG0352, which had been identified by real-time PCR. The results of CR3 blocking and lncRNA GAS5 gene silence or overexpression showed that the difference in IL-12 levels between P. gingivalis W83 and ΔPG0352 groups was associated with CR3, lncRNA GAS5 and miR-21. Thus it can be concluded that the sialidase-deficient strain is more easily cleared by attenuating CR3 activation， reducing the inhibition of lncRNA GAS5, inducing less miR-21 and more IL-12 in macrophages. These results indicate that inhibiting the activity of sialidase in P. gingivalis will cause rapid clearing by macrophages.